1999
DOI: 10.1110/ps.8.6.1362
|View full text |Cite
|
Sign up to set email alerts
|

New insight into the pH‐dependent conformational changes in bovine β‐lactoglobulin from Raman optical activity

Abstract: Abstract:We have studied the conformation of b-lactoglobulin in aqueous solution at room temperature over the pH range ;2.0-9.0 using vibrational Raman optical activity~ROA!. The ROA spectra clearly show that the basic up and down b-barrel core is preserved over the entire pH range, in agreement with other studies. However, from the shift of a sharp positive ROA band at ;1268 to ;1294 cm Ϫ1 on going from pH values below that of the Tanford transition, which is centered at pH ;7.5, to values above, the Tanford … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 37 publications
1
31
0
1
Order By: Relevance
“…ROA measures the difference of the Ramans cattered intensity between right and left circularly polarization and has become one of the prime techniques for determining absolute configurations of molecules [17][18][19][20] and conformers of biomolecules [21,22] in addition to ECD, VCD, andOR. [23,12] Quantum-mechanical calculationsa re very important for the assignment of ROA spectra, for instance, to assign the absolute configuration of chirally deuterated neopentane [24] and methyloxiranei ng as and liquid phases, [25,26] or the asymmetricc arboni nC HFClBr.…”
Section: Roa Spectroscopymentioning
confidence: 99%
“…ROA measures the difference of the Ramans cattered intensity between right and left circularly polarization and has become one of the prime techniques for determining absolute configurations of molecules [17][18][19][20] and conformers of biomolecules [21,22] in addition to ECD, VCD, andOR. [23,12] Quantum-mechanical calculationsa re very important for the assignment of ROA spectra, for instance, to assign the absolute configuration of chirally deuterated neopentane [24] and methyloxiranei ng as and liquid phases, [25,26] or the asymmetricc arboni nC HFClBr.…”
Section: Roa Spectroscopymentioning
confidence: 99%
“…Interestingly, a b-barrel protein, bovine b-lactoglobulin under pH 2.0 or 6.8, showed a positive ROA peak at 1268 cm 21 . 61 It was suggested that this peak originated from the type-I b-turn or inverse g-turn, but not so clear. This peak vanished under the alkalic pH, 61 suggesting a relation to the structural changes of turns and loops associated with the Tanford transition.…”
Section: Resultsmentioning
confidence: 99%
“…In native systems, when comparing pH 2.0 with 3.0 a considerable increase in interfacial viscoelastic modulus and its elastic part as well as a concurrent decrease in phase angle from 18.0°to 5.7°w as observed (p < 0.05) at the higher pH value. With a change in pH from 2.0 to 3.0 the quaternary structure of b-lactoglobulin changes from predominantly monomeric to dimeric, respectively (Blanch et al, 1999;Taulier and Chalikian, 2001) and is accompanied by a change in surface density of adsorbed proteins explaining the significant differences in IFT (Table 1). Regarding the fibrils, notable differences in dilatational elastic moduli E 0 between short and long fibrils were observed at pH 2.0 and 3.0.…”
Section: Interfacial Activity and Dilatational Rheology Of Native Andmentioning
confidence: 99%